Rule-in-Use for Community-Based Springs Management Faces Land Use Pressures: Lesson Learned from Manggarai District - Steni, Bernadinus; Kartodihardjo, Hariadi; Adiwibowo, Soeryo; Djakapermana, Ruchyat Deni (The Indonesian Journal of Socio-Legal Studies, 2024)
The struggle for water is one of the greatest immediate risks of the climate crisis. Therefore, the institutional challenge of water management is increasingly urgent and requires a number of consensuses to succeed, including community-based natural resource management (CBNRM). A key challenge to the traditional consensus for water conservation is the increasing need for land conversion due to population growth, which in turn deflects decision-making power away from traditional institutions towards external decision-makers such as regional governments. Using Ostrom's conceptual framework of rules of use, this research examines shifting spring water management in the context of Kabupaten Manggarai. The paper explores traditional rules of water management in the community and compares it to the institutional development of springs in four villages. Ultimately, it analyses the gap between the traditional rules of water management and the reality on the ground. The study finds that traditional community management of springs is subject to power contestation due to unclear institutional direction, which in turn emerges from opaque land and spatial planning policies and political decisions. These policies are overly economic and do not take into account traditional conservation and resources characteristics.